High mannoronic acid containing alginate affects the differentiation of Wharton's jelly-derived stem cells to hepatocyte-like cell - Saeed Azandeh; Darioush Bijan Nejad; Vahid Bayati; Foroug Shakoor; Negar Varaa; Bahman Cheraghian (Wolters Kluwer Medknow Publications, 2019)
For transplantation of cell into injured tissues, cells should be transferred to the damaged site through an adequate carrier. Nevertheless, the nutrient-limited and hypoxic condition in the carrier can bring about broad cell death. This study set to assess the impact of alginate concentrations on the differentiation and the proliferation of cells encapsulated in alginate hydrogels. Human Wharton's Jelly-derived Mesenchymal Stem Cells (HWJ-MSCs) were encapsulated in two concentrations of alginate hydrogel. Then, the proliferation and the hepatic differentiation were evaluated with an MTT assay and the enzyme-linked immunosorbent assay software and urea production. The results demonstrated that the proliferation of cell and urea production in 1.5% alginate concentration was higher than in 2.5% alginate concentration in the hydrogels of alginate. We deduce that the optimized alginate hydrogel concentration is necessary for achieving comparable cell activities in three-dimensional culture.